Penyuluhan Kesehatan dan Aktivitas Fisik Bersama Anak Jalanan dalam Mewujudkan SDGs dan Pancasila Sila ke-3 - Chalista Cheryl Yonatha; Angelica Crystalina; Sherly Marcellina; Ferdy Anthonius; Christian Siregar (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Health and physical activity counseling is one of the efforts to raise awareness and healthy lifestyle habits, especially for vulnerable groups such as street children. This article is a community service article based on participatory education that aims to increase street children's knowledge about healthy lifestyles and foster simple physical activity habits. This program is also in line with Sustainable Development Goals (SDGs) number 3, namely a healthy and prosperous life. This activity also helps strengthen the values ​​of togetherness and unity as contained in the 3rd principle of Pancasila, "Indonesian Unity". The approach to this activity is through basic health education about the importance of physical health, group exercise, and competitions that affect physical health. These competitions include group exercise activities, mingle squid games, and guessing styles. The service method is carried out through an educational and participatory approach, which includes filling out a pre-test to measure participants' initial knowledge, delivering health education materials, interactive physical activities in the form of simple exercises and games, and a post-test as an evaluation instrument to measure the increase in participants' understanding. The results of this activity showed a 21.7% increase in average understanding of the importance of health and simple physical activities, accompanied by a growing sense of community. This activity provided a practical contribution to non-formal health education for marginalized groups and strengthened community service implementation in accordance with Pancasila values ​​and the principles of the SDGs.